Trading privileges for support: the strategic co-optation of emerging powers into international institutions. Issue 3 (November 2019) - Kruck, Andreas; Zangl, Bernhard
Abstract: As emerging powers rise and established powers decline, international institutions come under pressure to adjust to new power realities. When and how do international institutions adapt to underlying global power shifts? We propose an (institutionalist) theory of strategic co-optation that differs from both (realist) accommodationist and (liberal) integrationist theories. Drawing on isolated treatments of strategic co-optation from other domains – domestic and international, autocratic and democratic, past and present – we develop a theory of strategic co-optation as a mode of institutional adaption to shifts in the global distribution of power. The theory specifies the concept, the conditions and the (unintended) consequences of strategic co-optation. We conceptualize co-optation as a specific form of adaptation where established powers trade institutional privileges for emerging powers' institutional support. We theorize the conditions under which emerging and established powers are (more or less) likely to strike a co-optation deal. In addition, we identify endogenous dynamics that may render co-optation precarious and thus subject to instabilities. While the ambition of this paper is primarily theoretical, we provide various empirical illustrations of how strategic co-optation is used to adapt international institutions to contemporary shifts in the global distribution of power.